The Legal Literature of Accounting: On Accountants by Diego del Castillo (Book). - Yamey, Basil S. (The Accounting Review, 1989)
Reviews the book "The Legal Literature of Accounting: On Accounts by Diego del Castillo," translated by Patti A. Mills.